Maternal behavior promotes resilience to adolescent stress in mice through a microglia-neuron axis - Hongyu Chen; Ruifeng Xu; Jianhao Wang; Feng Gao; Yida Lv; Xiang Li; Fang Li; Junqin Zhao; Xi Zhang; Jiabei Wang; Ruicheng Du; Yuke Shi; et al. (Nature Communications, 2025)
Abstract Early life experience modulates resilience to stress in later life. Previous research implicated maternal care as a key mediator of behavioral responses to the adversity in adolescence, but details of molecular mechanisms remain elusive. Here, we show social stress activates transcription factor C/EBPβ in mPFC neurons of adolescent mice, which transcriptionally upregulates Dnm1l and promotes mitochondrial dysfunction, thereby conferring stress susceptibility in adolescent mice. Moreover, different maternal separation differentially regulates adolescent stress susceptibility. Mechanistically, this differential effect depends on maternal behavior-stimulated IGF-1, which inhibits neuronal C/EBPβ through mTORC1-induced C/EBPβ-LIP translation. Furthermore, we identify maternal behavior-stimulated IGF-1 is mainly released from mPFC microglia. Notably, increased maternal care under an environmental enrichment condition or maternal behavior impairment induced by repeated MPOAEsr1+ cells inhibition in dams prevents or promotes stress susceptibility via microglial-to-neuronal IGF-1-C/EBPβ-DRP1 signaling. In this work, these findings have unveiled molecular mechanisms by which maternal behavior promotes stress resilience in adolescents.